(3GdeSdc Gdbhje aj eWGHbI JYdb GdNHQI HGdMGOK dJYdb GdYde GdbOjes - (3EHQGgje Hf MSf Hf TgGH GdOjf GdTgQGfj GdTgQRhQqj GdchQGfj, HQgGf GdOjf,J (B1101 (3g` s ((3XGgQI GdeOjfI GdefhQI s)
(3ChdgG (B:s
(3CeG HYO abO SCdJ CjOc HfhQg Bejf YeG PcQg GdTjN YHO GdhgGH GdTYQGfi ai cJGHg GdjhGbjJ hGdLhGgQ s
(3BNQgG (B:s
(3ceG jMji GdCQV GdejJI HhGHd GdeWQ GfJgi Je HMeO Gddg hYhfg hMSf Jhajbg hUdi Gddg Ydi eMeO s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B35 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B21s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3eLGejY WdYJ (B_ (3JhMjO (B585) s
Keywords: (3GdJhMjO hGdedd hGdfMds